Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Incipient aqueous alteration recorded by matrix metal in the most pristine CO chondrite Dominion Range 08006 - Shaofan Che; Adrian J. Brearley (Geochimica et Cosmochimica Acta, 2026)

Distribution and taxonomic composition of leptocephali and hydrographic structure from New Zealand to the South Equatorial Current - Michael J. Miller; Shun Watanabe; Robert Schabetsberger; Nioka Behan-Kitto; Grace F. Cawley; Niamh Smith; Alisha M. Gill; Alexandre Che-Pelicier; Juliet E. Saul; Abigail Sim; Therese C. Miller; Sajini Dissanayake; et al. (Regional Studies in Marine Science, 2026)

Formation mechanisms of foraminifera-dominated silt–sand sheets in the Baiyun Sag, South China Sea: The role of Kuroshio and North Pacific Intermediate Water - Chengkun Deng; Xiaojie Wei; Zhiqian Gao; Tailiang Fan; Zhongtao Zhang; Ronald J. Steel; Leyi Xu; Hairong Wang; Haojie Gao; Tiangui Che; Lingxue Peng (Marine Geology, 2026)

Underestimation of soil organic carbon by global spatially explicit soil datasets in Chinese urban greenspaces - Zidong Zhou; Yiming Xu; J. Aaron Hogan; Shikui Dong; Yike Wang; Qizheng Mao; Fayong Liu; Cuijuan Liao; Yunmeng Qin; Yunling Che; Jiang Zhang; Xinyu Zou; et al. (Journal of Cleaner Production, 2026)

Association between noise pollution exposure and incident breast cancer in the Sister Study - Brittney A. Gedeon; Che-Jung Chang; Peter James; Rena R. Jones; Alexandra J. White (Environmental Research, 2026)

Extract from the seedlings of Brassica oleracea var. italica (Brassicaceae) reduces tissue damage and alters inflammatory markers over time: development of new medications - Katherine M Warpeha; Cimran Nakum; Yahya Najjar; Aleksandra A. Gurgul; Chun-Tao Che; Thomas J. Park (Phytochemistry Letters, 2025)

Antibacterial mechanism of Malaysian Carey clay against food-borne Staphylococcus aureus - Nur Naqiyah Azmi; Nor Ainy Mahyudin; Wan Hasyera Wan Omar; Abdul Halim Abdullah; Roslan Ismail; Che Fauziah Ishak; Gary J. Sharples (Natural Product Research, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

P35-04 Efforts to Improve Nonclinical Guidelines for Enhancing the Safety of Prophylactic mRNA Vaccines in South Korea - J.-H. Che; G. Keum; B.-C. Kang; J.W. Yun; H. Youn; S.-M. Lee; J.-H. Nam (Toxicology Letters, 2025)

Twelve strategies for realizing the promise of ecopracticology - Steven J. Cooke; Marco Carlotti; Kgosietsile Velempini; Nathan Heavers; Zhifang Wang; Zoe Moula; Qinghe Hou; Andrew Howarth; Meagan Harper; Andrew N. Kadykalo; Yasuhisa Kondo; Yue Che; et al. (Socio-Ecological Practice Research, 2025)

Revisiting bibliometric methods in natural solvent research (Int J Environ Sci Technol. 2024 Jul 1) - P-Y Che; J Tian (International Journal of Environmental Science and Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Residential proximity to toxic metal-emitting industrial sites and toenail metal concentrations in a United States-wide prospective cohort - Meklit Daniel; Jennifer L. Ish; Jessica M. Madrigal; Che-Jung Chang; Kaitlyn G. Lawrence; Jared A. Fisher; Keith E. Levine; Brittany A. Trottier; Rena R. Jones; Dale P. Sandler; Alexandra J. White (Environmental Research, 2024)

Natural coral recovery despite negative population growth - Aziz J. Mulla; Vianney Denis; Che‐Hung Lin; Chia‐Ling Fong; Jia‐Ho Shiu; Yoko Nozawa (Ecology, 2024)
Demographic processes that ensure the recovery and resilience of marine populations are critical as climate change sends an increasing proportion on a trajectory of decline. Yet for some populations, recovery potential remains high. We conducted annual monitoring over 9 years (2012–2020) to assess the recovery of coral populations belonging to the genus Pocillopora . These populations experienced a catastrophic collapse following a severe typhoon in 2009. From the start of the monitoring period, high initial recruitment led to the establishment of a juvenile population that rapidly transitioned to sexually mature adults, which dominated the population within 6 years after the disturbance. As a result, coral cover increased from 1.1% to 20.2% during this time. To identify key demographic drivers of recovery and population growth rates (λ), we applied kernel‐resampled integral projection models (IPMs), constructing eight successive models to examine annual change. IPMs were able to capture reproductive traits as key demographic drivers over the initial 3 years, while individual growth was a continuous key demographic driver throughout the entire monitoring period. IPMs further detected a pulse of reproductive output subsequent to two further Category 5 typhoon events during the monitoring period, exemplifying key mechanisms of resilience for coral populations impacted by disturbance. Despite rapid recovery, (i.e., increased coral cover, individual colony growth, low mortality), IPMs estimated predominantly negative values of λ, indicating a declining population. Indeed, while λ translates to a change in the number of individuals, the recovery of coral populations can also be driven by an increase in the size of surviving colonies. Our results illustrate that accumulating long‐term data on historical dynamics and applying IPMs to extract demographic drivers are crucial for future predictions that are based on comprehensive and robust understandings of ecological change.

Identification of synthetic cathinone positional isomers using electron activated dissociation mass spectrometry - Peng Che; Christina Chang; Patrick Buzzini; Lavinia Stegemann; Jeroen Kool; J. Tyler Davidson; Isabelle Kohler (Analytica Chimica Acta, 2024)

Recycling waste polyethylene into fuels over Fe/USY catalyst: Evaluation on the catalytic activities of varied iron states - Zezhou Chen; Barry J. Erwin; Lei Che (Fuel, 2024)

Polyoxygenated cyclohexene derivatives and other constituents of Uvaria rufa stem - Aleksandra Gurgul; Zhenlong Wu; Kyu-Yeon Han; Gauri Shetye; Kongmany Sydara; Onevilay Souliya; Jeremy J. Johnson; Chun-Tao Che (Phytochemistry, 2023)

Electron activated dissociation - a complementary fragmentation technique to collision-induced dissociation for metabolite identification of synthetic cathinone positional isomers - Peng Che; J. Tyler Davidson; Jeroen Kool; Isabelle Kohler (Analytica Chimica Acta, 2023)

Chemical constituents of the stem of Marsypopetalum modestum and their bioactivities - Aleksandra Gurgul; Mirielle C Nauman; Zhenlong Wu; Gauri Shetye; Rui Ma; Isoo Youn; Onevilay Souliya; Jonathan Bisson; Jeremy J Johnson; Chun-Tao Che (Natural Product Research, 2023)

The important role of fluid chemistry in the hydrothermal alteration of ordinary chondrites: Insights from halite and sphalerite in the Sidi El Habib 001 (H5) meteorite - Shaofan Che; Kenneth J. Domanik; Yao-Jen Chang; Thomas J. Zega (Earth and Planetary Science Letters, 2023)

Hydrocracking of polyethylene to hydrocarbon fuels over Pt/USY catalysts: Assessment of the hydrogen donors - Zezhou Chen; Barry J. Erwin; Lei Che (Journal of Cleaner Production, 2023)

Penguindex: a Living Planet Index for Pygoscelis species penguins identifies key eras of population change - Emma J. Talis; Christian Che-Castaldo; Tom Hart; Louise McRae; Heather J. Lynch (Polar Biology, 2023)

Repeated applications of farm dairy effluent treated with poly-ferric sulphate did not adversely affect soil phosphorus availability, P fractions and pasture response — a 4-year field plot study - Xueying Che; Hong J. Di; Keith C. Cameron; Rosalind Dodd (Journal of Soils and Sediments, 2023)
Purpose Land application of farm dairy effluent (FDE) can cause phosphorus contamination of freshwater due to its high nutrient content especially phosphorus (P) in the animal dung. A novel FDE treatment technology has been developed that uses poly-ferric sulphate (PFS) to treat the FDE and recycle water for washing farmyard and reduce the risk of water pollution from P leaching from through the soil. It is important that the application of PFS-treated FDE (TE) does not cause any adverse impacts on soil fertility or plant growth when the TE is applied to the soil. Materials and methods A multi-year field plot study was conducted to determine the effect of repeat applications of FDE and PFS-treated FDE (TE) on soil P availability, P fractionations, plant yield and nutrient uptake. Eight applications of untreated FDE, TE and water as control were applied to replicated soil plots over the period of 4 years. The soil samples were collected on 1 December 2020, and nine pasture samples were harvested during the 2021–2022 dairy milking season. Measurements included soil chemical properties, soil phosphorous fractionations, plant biomass and plant phosphorus and nitrogen uptake. Results and discussion The results indicated that the majority of soil fertility indices and soil P fractions had no significant difference between the FDE and TE applications, with the exception of labile P which was significantly higher in the TE (122.7 mg kg −1 ) than in the FDE treatments (103.0 mg kg −1 ) at 0–10-cm soil depth and was also significantly higher in the TE (114.6 mg kg −1 ) than in the FDE treatments (74.0 mg kg −1 ) at 10–20-cm soil depth. Similarly, plant P uptakes and dry matter yields were also the same between the TE and FDE treatments with the average of being 54.4 kg P ha −1 and 12.8 t ha −1 , respectively. Conclusions Repeated applications of PFS-treated FDE had no adverse effect on soil P availability or plant growth when compared to untreated FDE application and had the potential to benefit soil fertility compared to control.

Investigating spatio-temporal variability of initial 230Th/232Th in intertidal corals - Hong-Wei Chiang; Belle Philibosian; Aron J. Meltzner; Chung-Che Wu; Chuan-Chou Shen; R. Lawrence Edwards; Chih-Kai Chuang; Bambang W. Suwargadi; Danny H. Natawidjaja (Quaternary Science Reviews, 2023)

In-situ formation of halite in the Sidi El Habib 001 (H5) ordinary chondrite: Implications for hydrothermal alteration in ordinary chondrite parent bodies - Shaofan Che; Kenneth J. Domanik; Thomas J. Zega (Geochimica et Cosmochimica Acta, 2023)

Assessment of toxic mechanisms and mode of action to three different levels of species for 14 antibiotics based on interspecies correlation, excess toxicity, and QSAR - Jin J. Li; Ya X. Yue; Jie F. Jiang; Sheng J. Shi; Hui X. Wu; Yuan H. Zhao; Fei F. Che (Chemosphere, 2023)

Thermal performance of a window shutter with a phase change material as a passive system for buildings in warm and cold climates of México - M. Che-Pan; E. Simá; A. Ávila-Hernández; J. Uriarte-Flores; R. Vargas-López (Energy and Buildings, 2023)

PEPT validated CFD-DEM model of aspherical particle motion in a spouted bed - Hanqiao Che; Mark Al-Shemmeri; Peter J. Fryer; Estefania Lopez-Quiroga; Tzany Kokalova Wheldon; Kit Windows-Yule (Chemical Engineering Journal, 2023)

Cytotoxic potential of Nephthea sp.-derived actinomycetes supported by metabolomics analysis - Omnia Hesham Abdelhafez; John Refaat Fahim; Mostafa E. Rateb; Che J. Ngwa; Gabriele Pradel; Usama Ramadan Abdelmohsen; Samar Yehia Desoukey; Mohamed Salah Kamel (Natural Product Research, 2022)

Critical Risk Indicators (CRIs) for the electric power grid: a survey and discussion of interconnected effects - Judy P. Che-Castaldo; Rémi Cousin; Stefani Daryanto; Grace Deng; Mei-Ling E. Feng; Rajesh K. Gupta; Dezhi Hong; Ryan M. McGranaghan; Olukunle O. Owolabi; Tianyi Qu; Wei Ren; Toryn L. J. Schafer; et al. (Environment Systems and Decisions, 2021)

Photo-movement of coral larvae influences vertical positioning in the ocean - Aziz J. Mulla; Che-Hung Lin; Shunichi Takahashi; Yoko Nozawa (Coral Reefs, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Efficient segment-based ground filtering and adaptive road detection from mobile light detection and ranging (LiDAR) data - Erzhuo Che; Michael J Olsen; Jaehoon Jung (International Journal of Remote Sensing, 2021)

Influence of Silver Nanoparticle–Based Coating on Calcareous Rock Surfaces on Microbial Biofilm Colonization in Intertidal Environments in Campeche, Mexico - Juan Carlos Camacho-Chab; Benjamín O. Ortega-Morales; Christine Gaylarde; Juan E. Pereañez-Sacarías; Hilda P. León-Tejera; Rodrigo E. Tun-Che; Radames J. Álvarez-Zapata; Augusto I. Almeyda-Cen; William Talavera-Pech; Juan F. Illescas-Salinas (Water, Air, & Soil Pollution, 2021)

Sea Urchins Play an Increasingly Important Role for Coral Resilience Across Reefs in Taiwan - Viet D. H. Dang; Pak-Yin Cheung; Chia-Ling Fong; Aziz J. Mulla; Jia-Ho Shiu; Che-Hung Lin; Yoko Nozawa (Frontiers in Marine Science, 2020)
Herbivores are an important functional group that control algae, create new space, and promote recruitment for coral recovery. However, on many coral reefs, overfishing has greatly decreased the density of herbivores, especially fishes and gastropods, impairing coral resilience. On such overfished reefs, remnant herbivores that are not target species of local fisheries, e.g., sea urchins, are expected to play an increasingly important role, yet few studies, except for those in the Caribbean and Kenya have examined non-fish herbivores in relation to coral resilience. Here, we conducted field surveys at 30 sites along three coral reefs in Taiwan between 2016 and 2017, to examine the relative importance of six key factors for coral resilience: herbivore abundance (fishes, gastropods, sea urchins), coral cover, macroalgal cover, habitat complexity, water depth, and wave exposure. The density of juvenile coral was used as a proxy of coral resilience. Diadematid sea urchins ( Echinothrix spp. and Diadema spp.) dominated most sites (19 of 30 sites) and multivariable regression models showed sea urchin density as the best positive predictor of coral juvenile density. The results elucidated the increasing role diadematid sea urchins play as remnant herbivores on overfished coral reefs in Taiwan. Given that overfishing is a widespread issue, this phenomenon may be occurring globally. More studies are needed to examine the role of remnant, but often ignored, sea urchin herbivory on coral resilience. Reef managers should consider monitoring locally remnant herbivores and incorporating them into management strategies.

The role of reactive oxygen species in the virulence of wheat leaf rust fungus Puccinia triticina - Xiben Wang; Mingzhe Z. Che; Hala B. Khalil; Brent D. McCallum; Guus Bakkeren; Christof Rampitsch; Barry J. Saville (Environmental Microbiology, 2020)
Summary Reactive oxygen species (ROS) play an important role during host–pathogen interactions and are often an indication of induced host defence responses. In this study, we demonstrate for the first time that Puccinia triticina ( Pt ) generates ROS, including superoxide, H 2 O 2 and hydroxyl radicals, during wheat infection. Through pharmacological inhibition, we found that ROS are critical for both Pt urediniospore germination and pathogenic development on wheat. A comparative RNA‐Seq analysis of different stages of Pt infection process revealed 291 putative Pt genes associated with the oxidation–reduction process. Thirty‐seven of these genes encode known proteins. The expressions of five Pt genes, including PtNoxA , PtNoxB , PtNoxR , PtCat and PtSod , were subsequently verified using RT‐qPCR analysis. The results show that the expressions of PtNoxA , PtNoxB , PtNoxR , PtCat and PtSod are up‐regulated during urediniospore germination. In comparison, the expressions of PtNoxA , PtNoxB , PtNoxR and PtCat are down‐regulated during wheat infection from 12 to 120 h after inoculation (HAI), whereas the expression of PtSod is up‐regulated with a peak of expression at 120 HAI. We conclude that ROS are critical for the full virulence of Pt and a coordinate down‐regulation of PtNox genes may be important for successful infection in wheat.

Differences in dry-bulb temperature do not influence moderate-duration exercise performance in warm environments when vapor pressure is equivalent - Tze-Huan Lei; Zachary J. Schlader; Ahmad Munir Che Muhamed; Huixin Zheng; Stephen R. Stannard; Narihiko Kondo; James D. Cotter; Toby Mündel (European Journal of Applied Physiology, 2020)

Regional breeding bird assessment of the Antarctic Peninsula - Michael B. Schrimpf; Christian Che-Castaldo; Heather J. Lynch (Polar Biology, 2020)

Laboratory Investigation of Liquid Injectivity in Surfactant-Alternating-Gas Foam Enhanced Oil Recovery - J. Gong; S. Vincent-Bonnieu; R. Z. Kamarul Bahrim; C. A. N. B. Che Mamat; J. Groenenboom; R. Farajzadeh; W. R. Rossen (Transport in Porous Media, 2020)

The joint impact of smoking plus alcohol drinking on treatment of pulmonary tuberculosis - Y. Ma; N.-Y. Che; Y.-H. Liu; W. Shu; J. Du; S.-H. Xie; Liang Li (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Novel Polymeric Valve for Transcatheter Aortic Valve Replacement Applications: In Vitro Hemodynamic Study - Oren M. Rotman; Brandon Kovarovic; Wei-Che Chiu; Matteo Bianchi; Gil Marom; Marvin J. Slepian; Danny Bluestein (Annals of Biomedical Engineering, 2019)

Strong evidence for changing fish reproductive phenology under climate warming on the Tibetan Plateau - Juan Tao; Dekui He; Mark J. Kennard; Chengzhi Ding; Stuart E. Bunn; Chunlong Liu; Yintao Jia; Rongxiao Che; Yifeng Chen (Global Change Biology, 2018)
Phenological responses to climate change have been widely observed and have profound and lasting effects on ecosystems and biodiversity. However, compared to terrestrial ecosystems, the long‐term effects of climate change on species’ phenology are poorly understood in aquatic ecosystems. Understanding the long‐term changes in fish reproductive phenology is essential for predicting population dynamics and for informing management strategies, but is currently hampered by the requirement for intensive field observations and larval identification. In this study, a very low‐frequency sampling of juveniles and adults combined with otolith measurements (long axis length of the first annulus; LAFA ) of an endemic Tibetan Plateau fish ( Gymnocypris selincuoensis ) was used to examine changes in reproductive phenology associated with climate changes from the 1970s to 2000s. Assigning individual fish to their appropriate calendar year class was assisted by dendrochronological methods (crossdating). The results demonstrated that LAFA was significantly and positively associated with temperature and growing season length. To separate the effects of temperature and the growing season length on LAFA growth, measurements of larval otoliths from different sites were conducted and revealed that daily increment additions were the main contributor (46.3%), while temperature contributed less (12.0%). Using constructed water‐air temperature relationships and historical air temperature records, we found that the reproductive phenology of G. selincuoensis was strongly advanced in the spring during the 1970s and 1990s, while the increased growing season length in the 2000s was mainly due to a delayed onset of winter. The reproductive phenology of G. selincuoensis advanced 2.9 days per decade on average from the 1970s to 2000s, and may have effects on recruitment success and population dynamics of this species and other biota in the ecosystem via the food web. The methods used in this study are applicable for studying reproductive phenological changes across a wide range of species and ecosystems.

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

Overexpression of an Aeluropus littoralis Parl. potassium transporter gene, AlHAK1, in cotton enhances potassium uptake and salt tolerance - J. F. Liu; S. L. Zhang; H. L. Tang; L. Z. Wu; L. J. Dong; L. D. Liu; W. L. Che (Euphytica, 2015)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Induction of Experimental Autoimmune Encephalomyelitis With Recombinant Human Myelin Oligodendrocyte Glycoprotein in Incomplete Freund’s Adjuvant in Three Non-human Primate Species - Krista G. Haanstra; S. Anwar Jagessar; Anne-Laure Bauchet; Mireille Doussau; Claire-Maëlle Fovet; Nicole Heijmans; Sam O. Hofman; Jennifer van Lubeek-Veth; Jeffrey J. Bajramovic; Yolanda S. Kap; Jon D. Laman; Hélène Touin; et al. (Journal of Neuroimmune Pharmacology, 2013)

The (TTTA) n polymorphism in intron 4 of CYP19 and the polycystic ovary syndrome risk in a Chinese population - P. Xu; X. L. Zhang; G. B. Xie; C. W. Zhang; S. M. Shen; X. X. Zhang; Y. X. Cao; W. J. Wang; Y. N. Che; Y. J. Xia; X. K. Wu; L. Yi; et al. (Molecular Biology Reports, 2013)

Global transcriptome analysis and identification of a CONSTANS-like gene family in the orchid Erycina pusilla - Ming-Lun Chou; Ming-Che Shih; Ming-Tsair Chan; Shih-Yi Liao; Chen-Tran Hsu; Yao-Ting Haung; Jeremy J. W. Chen; Der-Chih Liao; Fu-Hui Wu; Choun-Sea Lin (Planta, 2013)

Effect of two maximal isometric contractions on eccentric exercise-induced muscle damage of the elbow flexors - Trevor C. Chen; Hsin-Lian Chen; Ming-Ju Lin; Che-Hsiu Chen; Alan J. Pearce; Kazunori Nosaka (European Journal of Applied Physiology, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Human temperature regulation when given the opportunity to behave - Zachary J. Schlader; Blake G. Perry; M. Rahimi Che Jusoh; Lynette D. Hodges; Stephen R. Stannard; Toby Mündel (European Journal of Applied Physiology, 2013)

Development of monoclonal antibody-based galactomannoprotein antigen-capture ELISAs to detect Aspergillus fumigatus infection in the invasive aspergillosis rabbit models - Z.-Y. Wang; J.-P. Cai; L.-W. Qiu; W. Hao; Y.-X. Pan; E. T. K. Tung; C. C. Y. Lau; P. C. Y. Woo; S. K. P. Lau; K.-Y. Yuen; X.-Y. Che (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A Review on Fish Lipid: Composition and Changes During Cooking Methods - Y. Moradi; J. Bakar; A. A. Motalebi; S. H. Syed Muhamad; Y. Che Man (Journal of Aquatic Food Product Technology, 2011)

Systematic documentation of landslide events in Limbe area (Mt Cameroon Volcano, SW Cameroon): geometry, controlling, and triggering factors - V. B. Che; M. Kervyn; G. G. J. Ernst; P. Trefois; S. Ayonghe; P. Jacobs; E. Van Ranst; C. E. Suh (Natural Hazards, 2011)

Impact analysis of MODIS band-to-band registration on its measurements and science data products - Yong Xie; Xiaoxiong Xiong; John J. Qu; Nianzeng Che; Michael E. Summers (International Journal of Remote Sensing, 2011)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Haze trends over the capital cities of 31 provinces in China, 1981–2005 - Huizheng Che; Xiaoye Zhang; Yang Li; Zijiang Zhou; John J. Qu; Xianjun Hao (Theoretical and Applied Climatology, 2009)

On the use of SSR markers for the genetic characterization of the Agropyron cristatum (L.) Gaertn. in Northern China - Y. H. Che; H. J. Li; Y. P. Yang; X. M. Yang; X. Q. Li; L. H. Li (Genetic Resources and Crop Evolution, 2008)

Smoke plume detection in the eastern United States using MODIS - Y. Xie; J. J. Qu; X. Xiong; X. Hao; N. Che; W. Sommers (International Journal of Remote Sensing, 2007)

Analysis of sky conditions using 40 year records of solar radiation data in China - H. Z. Che; G. Y. Shi; X. Y. Zhang; J. Q. Zhao; Y. Li (Theoretical and Applied Climatology, 2007)

Gene expression and immunolocalisation of a calcium-activated chloride channel during the stratification of cultivated and developing corneal epithelium - Che J. Connon; Satoshi Kawasaki; Melody Liles; Noriko Koizumi; Kenta Yamasaki; Takahiro Nakamura; Andrew J. Quantock; Shigeru Kinoshita (Cell and Tissue Research, 2006)

Double-antigen sandwich ELISA for detection of antibodies to SARS-associated coronavirus in human serum - S. Chen; D. Lu; M. Zhang; J. Che; Z. Yin; S. Zhang; W. Zhang; X. Bo; Y. Ding; S. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

A neutral variant involved in a complex CFTR allele contributes to a severe cystic fibrosis phenotype - Jrme Clain; Jacqueline Lehmann-Che; Emmanuelle Girodon; Joanna Lipecka; Aleksander Edelman; Michel Goossens; Pascale Fanen (Human Genetics, 2005)

Heavy metals in soils and crops in Southeast Asia - Bernhard A. Zarcinas; Che Fauziah Ishak; Mike J. McLaughlin; Gill Cozens (Environmental Geochemistry and Health, 2004)

Airborne hyperspectral detection of microbial mat pigmentation in Rangiroa atoll (French Polynesia) - Serge Andréfouët1; Claude Payri; Eric J. Hochberg; Lydie Mao Che; Marlin J. Atkinson (Limnology and Oceanography, 2003)
The pigmentation of a cyanobacterial mat located in Rangiroa atoll (French Polynesia) was characterized using low‐altitude (500 m) Compact Airborne Spectrometer Imager hyperspectral measurements. Peaks in second and fourth derivatives of the reflective absorptance can be explained by chlorophyll and carotenoid pigments, which were independently identified by high‐pressure liquid chromatography. Phycobilin pigments were also detected from airborne measurements. The study confirms the extensibility of derivative spectroscopy from in vivo to highresolution remote sensing measurements for biology and geochemistry investigations in marine communities.